THE PERCEPTIONS OF ENGLISH STUDY PROGRAM UNIVERSITAS RIAU STUDENTS ON ONLINE LEARNING AS THE IMPACT OF COVID-19 - Hasanah, Salfira; Azhar, Fadly; Eliwarti, Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aimed to find out the Perceptions of English Study ProgramUniversitas Riau Students on Online Learning as the Impact of COVID-19. Theresearch method is descriptive quantitative research. Random sampling technique wasapplied to decide the sample as the participants. The instrument of this research was aquestionnaire categorized into four components of students’perceptions on online learning: Assessment of Educational System Quality from a Perspective (ESQP), Information Quality Perspective (IQP), Ease of Use Perspective (EUP), Usefulness Perspective (UFP). The finding shows that the perceptions of English Study Program Universitas Riau Students on Online Learning as the Impact of COVID-19 are in Agree category. This study recommends that students are expected to join online learning as joining offline learning in order to present the the inline perceptions of each items for the components of online learning. Besides, in order to create successful online learning outcomes in educational settings, the lecturers are expected to incorporate digital technologies and synchronous teaching methods. The finding of this study also recommends the researchers to conduct a research on the students’ perceptions on the feedback of assignments and exams.Key Words: Online Learning; the Impact of COVID-19; Perception